Desain Proses Pengolahan Minyak Sektor Onshore Kapasitas 800 BOPD Dengan Luasan Industri Efektif - Rajoki Siahaan, Gomgom Parulian; Suarda, Made; Ghurri, Ainul (Teknik Desain Mekanika, 2022)
Abstract Beside of environmental sustainability, the optimization of the operation area of oil industry also has an impact on reducing costs and ease of controlling the scope of the industry. In this study, an onshore gathering station area will be designed that optimizes the area of operation with a production capacity of 800 BOPD. The 3-dimensional design is carried out with Smartplant 3D software which can also support the analysis and calculation of the weight of industrial components. From the calculation results and 3 dimensional design, to meet the production capacity of 800 BOPD, an industrial design was obtained which includes 6 separators, 8 gas boots, 14 pumps, 4 flow splitter, 2 vapor recovery, 2 wash tanks, and 2 shipping tanks covering an area of 3,357 m2. Industrial area is more effective with a maximum pump power of 0.08 MW. Keywords : oil and gas industry design, smartplant 3D, piping system, 800 BOPD